Enhanced boiling heat transfer on binary surfaces. (November 2017) - Holguin, Ryan; Kota, Krishna; Wootton, Stephen; Chen, Ruey-Hung; Ross, Sean
Highlights: Practicable, robust, scalable binary surfaces were pursued for boiling enhancement. The current boiling performance limits were pushed for PF-5060 on these surfaces. Presence of a trapped non-boiling liquid in the binary surface enhances boiling. Abstract: A novel idea for the improvement of boiling heat transfer is that of a binary surface – where a non-boiling liquid coats sub-surface irregularities and aids in heat transfer to the primary working fluid. The threefold goal of this effort was to: (i) prepare durable, low-cost, scalable binary surfaces for boiling heat transfer enhancement, (ii) conduct pool boiling experiments on these surfaces, and (iii) derive the physical mechanisms perceived as responsible for the observed boiling enhancements. Accordingly, robust binary surfaces were prepared on copper using a facile, scalable bulk micro-manufacturing approach. These surfaces consist of numerous micro-/nano-cavities filled by a non-boiling liquid creating puddles around solid islands. Boiling experiments were carried out using a dielectric liquid, PF-5060, as the primary working fluid (the boiling liquid). It was observed that, compared to a smooth/plain copper surface, a binary copper surface, with water as the NBL, was able to simultaneously enhance the maximum heat flux limit by ∼2.2 times and the average heat transfer coefficient by ∼7.5 times. A maximum heat flux of 35.06 W/cm 2 was recorded, which is higher than the enhancements reported so far in literature for the pool boiling of PF-5060 on any enhanced surface. It was further found that decreasing the contact angle of the non-boiling liquid on the binary surface enhances both the heat transfer coefficient and the maximum heat flux limit.